2018
DOI: 10.1002/mc.22898
|View full text |Cite
|
Sign up to set email alerts
|

ZNF326 promotes a malignant phenotype of breast cancer by interacting with DBC1

Abstract: The biological role and underlying mechanism of action of zinc-finger protein 326 (ZNF326) in malignant tumors, including breast cancer, are still not clear. In this study, we detected high expression of ZNF326 in breast cancer specimens (60/111, 54.1%) and breast cancer cell lines (7/7); the expression level of ZNF326 was inversely associated with advanced pTNM stage (P = 0.002), positive lymph node metastasis (P = 0.004), poor prognosis in patients with breast cancer (P = 0.0097), and ER/PR/Her2 status (P = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…However, taken together, our results particularly with increased AKT1 signaling and anchorage independence assay show that DBC1 over-expression in U2OS cells promotes oncogenic pathways. These results are consistent with some recent reports also suggesting the oncogenic role of DBC1 (21)(22)(23).…”
Section: Energy Deficit Is Critical For the Induction Of Mitotic Arresupporting
confidence: 94%
“…However, taken together, our results particularly with increased AKT1 signaling and anchorage independence assay show that DBC1 over-expression in U2OS cells promotes oncogenic pathways. These results are consistent with some recent reports also suggesting the oncogenic role of DBC1 (21)(22)(23).…”
Section: Energy Deficit Is Critical For the Induction Of Mitotic Arresupporting
confidence: 94%
“…Furthermore, we recover the link to the interaction of MALAT1 with DBC1 [22]. While we did not directly enrich DBC1 as an interactor of Malat1, we identified Zfp326 that interacts directly with DBC1 [30,31]. We also detected binding of Elavl1 (also known as HuR) to MALAT1 previously reported to form a complex that represses transcription [32].…”
Section: Discussionmentioning
confidence: 50%
“…We found that lncRNA 604 binds to the nuclear transcription factor ZNF326 and could positively regulate its expression. Furthermore, we demonstrated that ZNF326 could accelerate the occurrence of EMT ( 29 , 30 ). Therefore, we also concluded that lncRNA 604 could promote the metastasis of CRC by regulating ZNF326 in the nucleus.…”
Section: Discussionmentioning
confidence: 79%